2018
DOI: 10.1111/apce.12188
|View full text |Cite
|
Sign up to set email alerts
|

Development Ngos: Basic Facts

Abstract: This paper systematically reviews the empirical literature on development nongovernmental organisations (NGOs), drawing both on quantitative and qualitative analyses, and constructs a set of basic facts about these organisations. These facts concern the size of the development NGO sector and its evolution, the funding of NGOs, the allocation of NGO aid and projects across beneficiary countries, the relationship of NGOs with beneficiaries, and the phenomenon of globalisation of development NGOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 68 publications
(129 reference statements)
0
17
0
Order By: Relevance
“…Our model relates to Goldman and Slezak's (2006), Burns and Kedia's (2006), Beyer et al's (2014), Thakor's (2015) on designing optimal contracts under potential strategic information disclosure of firms, and Aldeshev et al (2018) on the misbehaviours of international NGOs. Relatedly, we contribute to the growing literature on the theory of NGO regulation and monitoring (Auriol and Brilon, 2018;Aldashev and Navarra, 2018). In contrast to these models, we focus on the trade-off and the oversight mechanism as the key explanations for charities' misreporting behaviour.…”
Section: The Authorsmentioning
confidence: 99%
“…Our model relates to Goldman and Slezak's (2006), Burns and Kedia's (2006), Beyer et al's (2014), Thakor's (2015) on designing optimal contracts under potential strategic information disclosure of firms, and Aldeshev et al (2018) on the misbehaviours of international NGOs. Relatedly, we contribute to the growing literature on the theory of NGO regulation and monitoring (Auriol and Brilon, 2018;Aldashev and Navarra, 2018). In contrast to these models, we focus on the trade-off and the oversight mechanism as the key explanations for charities' misreporting behaviour.…”
Section: The Authorsmentioning
confidence: 99%
“…From this perspective, the operators would become an extension of the State and implement a diversity of actions and strategies such as PPANs; likewise, a comprehensive menu of entities with interference in the entire spectrum of policies would proliferate, from their design, including their implementation and evaluation. Several authors analyze how non-governmental entities play an active role in implementing social policies, particularly those of health and nutrition, not only in Latin America but also in other continents such as Africa and Asia [32][33][34][35][36] . During the development period of this research, some complaints about severe irregularities in child care by private operators were made, which showed that said entities had found a source of enrichment in the programs' operation while not complying with the function for which they were recruited.…”
Section: Discussionmentioning
confidence: 99%
“…It was that reason, Kim (2000) argues that the services provided by government and private sector were not no longer satisfying the people's needs; this then brought about the emergence of NGOs as the third sector in development. On the same view, Aldashev and Navarra (2018) argue that from the 1950s, the work of NGOs started to diversify to service the needs of the needy. Hence, NGOs were motivated to serve the needs of the communities; it is with that reason, Ashmawy (2017) The results show that some NGOs claim to be transparent and accountable, but some fail to provide accurate information in their annual reports.…”
Section: Findings and Discussionmentioning
confidence: 99%